A case of adenocarcinoma with enteroblastic differentiation of the ampulla of Vater. Issue 4 (27th March 2016) - Mitsuma, Koko; Taniguchi, Hirokazu; Kishi, Yoji; Hiraoka, Nobuyoshi
Abstract : Cancer of the ampulla of Vater is rare, though it has various histological types and its histogenesis is fascinating in view of the anatomically complex nature of the ampulla. Fetal gut‐like adenocarcinoma, usually found in the stomach, can also develop in the ampullary region in extremely rare cases. Here we present a case of ampullary adenocarcinoma with enteroblastic and neuroendocrine differentiation. A 55‐year‐old woman presented with an epigastric pain. Endoscopic examination revealed a 2‐cm submucosal tumor‐like lesion in the ampulla. The surgical specimen showed that an exposed protruding type of tumor appeared as a well‐demarcated whitish‐yellow solid mass. Microscopically, the tumor had proliferated in the common channel and invaded the duodenal submucosa with mucosal lesion of intestinal‐type adenocarcinoma. The main tumor consisted of three different histological types showing transitional areas: adenocarcinoma with enteroblastic differentiation (ENT), neuroendocrine carcinoma (NEC), and well differentiated adenocarcinoma (WEL). Morphologically the ENT resembled fetal gut and immunohistochemically expressed SALL4 and glypican 3. The WEL was positive for CK20 and CDX2, revealing an intestinal‐type phenotype. AFP and HepPar1 were not evident in any part of the lesion. We speculated this tumor had arisen from intestinal‐type adenocarcinoma of the common channel and acquired enteroblastic and neuroendocrine differentiation during growth.